2014
DOI: 10.1002/cssc.201400079
|View full text |Cite
|
Sign up to set email alerts
|

In situ Observation of Radicals and Molecular Products During Lignin Pyrolysis

Abstract: Lignin pyrolysis is a promising method for the sustainable production of phenolic compounds from biomass. However, detailed knowledge about the radicals involved in this process and their influence on the molecular products is missing. Herein, we report on the pyrolysis of hard- and softwood Klason lignins under inert gas conditions in a temperature range between 350-550 °C. During the pyrolysis process, the formed radicals were detected by in situ high-temperature electron paramagnetic resonance spectroscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 47 publications
4
70
0
Order By: Relevance
“…The OL signal from the C c AO group (64-61 ppm) was also lower than that of AL and MWL due to the dissociation of hydroxyls and esters linked with C c (Sun et al, 2000). The signals at 57-54 ppm are ascribed to methoxy groups, and play an important role in the lignin pyrolysis (Bährle et al, 2014;Wang et al, 2009). KL contains the lowest content of methoxyl, which was eliminated during the Klason treatment, as reported in previous studies (Akiyama et al, 2003;Kim et al, 2013).…”
Section: Structural Features Of Ligninsupporting
confidence: 59%
See 1 more Smart Citation
“…The OL signal from the C c AO group (64-61 ppm) was also lower than that of AL and MWL due to the dissociation of hydroxyls and esters linked with C c (Sun et al, 2000). The signals at 57-54 ppm are ascribed to methoxy groups, and play an important role in the lignin pyrolysis (Bährle et al, 2014;Wang et al, 2009). KL contains the lowest content of methoxyl, which was eliminated during the Klason treatment, as reported in previous studies (Akiyama et al, 2003;Kim et al, 2013).…”
Section: Structural Features Of Ligninsupporting
confidence: 59%
“…Yang et al (2007) found that AL decomposes over a wide temperature range of 160-900°C, and the final solid char yield was about 40%, much higher than that of cellulose pyrolysis. Bährle et al (2014) used KL as a model compound for comparing the pyrolysis behaviors of hardwood and softwood lignins. They suggested that radical formation during hardwood KL pyrolysis was more frequent than that of softwood KL pyrolysis, and was mainly due to high methoxy group content in hardwood KL.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to cellulose, hemicellulose and lignin pyrolysis investigation started receiving attention much later (Bährle et al, 2014;Collard and Blin, 2014;Kandziolka et al, 2014). Huang et al (2012) used xylose as a model compound to investigate pyrolysis pathways of hemicellulose, implementing DFT methods.…”
Section: Hemi-cellulose and Lignin Pyrolysismentioning
confidence: 99%
“…Wang et al 2009 performed pyrolysis of lignins isolated from hardwood and softwood, and found that methoxy group content has a significant influence on the pyrolysis of lignin. Bährle et al 2014 used Klason lignin for comparing the pyrolysis behavior of hardwood and softwood lignins. They suggested that radical formation during hardwood Klason lignin pyrolysis was more frequent than that of softwood Klason lignin pyrolysis, and was mainly due to high methoxy group content in hardwood Klason lignin (Bährle et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bährle et al 2014 used Klason lignin for comparing the pyrolysis behavior of hardwood and softwood lignins. They suggested that radical formation during hardwood Klason lignin pyrolysis was more frequent than that of softwood Klason lignin pyrolysis, and was mainly due to high methoxy group content in hardwood Klason lignin (Bährle et al 2014).…”
Section: Introductionmentioning
confidence: 99%